2018
DOI: 10.31230/osf.io/be7xq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation social science: Understanding and integrating human dimensions to improve conservation

Abstract: It has long been claimed that a better understanding of human or social dimensions of environmental issues will improve conservation. The social sciences are one important means through which researchers and practitioners can attain that better understanding. Yet, a lack of awareness of the scope and uncertainty about the purpose of the conservation social sciences impedes the conservation community's effective engagement with the human dimensions. This paper examines the scope and purpose of eighteen subfield… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
215
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(220 citation statements)
references
References 166 publications
(258 reference statements)
2
215
0
2
Order By: Relevance
“…Focus group discussion has had broad appeal as a research tool, as evidenced by this review. Although the use of focus group discussion as a research technique has been dominant in the other disciplines such as sociology and psychology, its use has recently grown in the conservation social science research (Bennett et al., ; Khadka et al., ; Paloniemi et al., ). During this review, we observed that researchers in conservation have not adequately reported on the methodological choices from planning to data analysis.…”
Section: Geographical Distribution Of the Use Of Focus Group Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus group discussion has had broad appeal as a research tool, as evidenced by this review. Although the use of focus group discussion as a research technique has been dominant in the other disciplines such as sociology and psychology, its use has recently grown in the conservation social science research (Bennett et al., ; Khadka et al., ; Paloniemi et al., ). During this review, we observed that researchers in conservation have not adequately reported on the methodological choices from planning to data analysis.…”
Section: Geographical Distribution Of the Use Of Focus Group Discussionmentioning
confidence: 99%
“…Conservation social science has come of age (Bennett et al., ). From being an outlier and on the sidelines of the discourse on conservation, the importance of understanding human perspectives is now centre stage in conservation decision making (Bennett et al., ; Khadka, Hujala, Wolfslehner, & Vacik, ; Paloniemi et al., ). Within the repertoire of tools that conservation biologists can use, focus group discussion is a commonly used method.…”
Section: Introductionmentioning
confidence: 99%
“…Since biodiversity conservation is also a social construct (Fischer & Young, ), its management requires an explicit recognition of the dynamics of shifting perceptions (framings) and goals of conservation (Brown & Everard, ; Mace, ). Failing to integrate the human dimension in conservation often leads to less effective interventions (Bennett et al., ). This is in contrast to the current paradigm of mechanistic underpinnings of solving decision‐making problems (Gregory et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Adem Esmail & Geneletti, ). The call for inter‐ and trans‐disciplinarity resonates in both the science (Bennett et al., ; Mace, ; Tallis et al., ) and policy communities (IPBES, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation